Pelagic metabolism in the waters of the Great Barrier Reef. (14th June 2013) - McKinnon, A. D.; Logan, M.; Castine, S. A.; Duggan, S.
Abstract : Pelagic metabolism (community respiration [CR] and net community production [NCP]) were measured in oxygen flux experiments at 14 locations in waters of the Great Barrier Reef (GBR) lagoon between 16°S and 23°S during the dry seasons of 2008 and 2009 and the wet seasons of 2009 and 2010. These were compared to similar experiments conducted in the wet season of 2005 in the far northern GBR (14°S). Seasonality (wet and dry season) was the greatest determinant of respiration rate, with median CR values of 1.85 mmol O2 m −3 d −1 in the dry season and 2.87 mmol O2 m −3 d −1 in the wet season. NCP normally ranged up to 9.16 mmol O2 m −3 d −1, depending on depth and phytoplankton biomass, though an extreme value of 14.96 mmol O2 m −3 d −1 occurred during flood conditions. Cross‐shelf effects had a strong influence on physicochemical variables but weaker effects on both CR and NCP, though both were higher inshore. All but two stations were net autotrophic, with a median ratio of gross primary production : CR of 1.5. Area‐specific CR was 72 ± 23 standard deviation (SD) mmol O2 m −2 d −1 in the dry season and 94 ± 27 SD mmol O2 m −2 d −1 in the wet season. Area‐specific NCP was lower in the dry season (41 ± 33 SD mmol O2 m −2 d −1 ) than in the wet season (55 ± 54 SD mmol O2 m −2 d −1 ). Peaks in area‐specific NCP were associated with floods, intrusions of nutrient‐rich sub‐thermocline Coral Sea water, and localized phytoplankton blooms but otherwise showed few seasonal or spatial trends. Overall, CR in GBR lagoon waters was comparable to rates in oligotrophic oceanic waters, but NCP was more typical of shelf systems.